Kausalitas Perkembangan Pariwisata dan Pertumbuhan Ekonomi di Indonesia - Florentinus Nugro Hardianto (Seminar Nasional Penelitian dan Abdimas, 2023)
This study aims to analyze the causal relationship between tourism development and economic growth in Indonesia. The data analysis method used is Granger causality analysis. The results of the study indicate variations in the causal relationship between economic growth and tourism development. The variation here refers to the fact that the causal relationship between the two variables can be significant or not depending on the selected indicator variables and the number of lags used in the analysis. For significant relationships, the results indicate that the relationship between the two variables can be either one-way or two-way. One-way relationship means that one variable affects the other variable. Two-way relationship means that both variables influence each other. This research is expected to benefit tourism industry practitioners and government as important input in evaluating the relationship between tourism development and economic growth in Indonesia, for the academic community as an additional empirical study on the relationship between tourism development and economic growth in Indonesia, and for the researchers themselves as an effort to contribute in the field of tourism and specifically related to the relationship between tourism development and economic growth in Indonesia. Keywords: tourism development, economic growth, Granger causality, Indonesia